Temporalis Fascia Lateral or Medial Side Up In Underlay Tympanoplasty Type – I Does It Makes A Difference? - Latifi, Asrar Ahmed; Syed, Shahid Raza (Journal of Otolaryngology Advances, 2015)
Objectives: The study was aimed to find out which of the two techniques, medial or lateral side of the temporalis fascia graft was better in underlay method for correcting the perforations of the tympanic membrane keeping all other factors constant. Methods: We designed a prospective randomized study from Jan 2010 to Jan 2013 at Buraidah Central Hospital, Al Qassim, Saudi Arabia. Eighty patients having dry central; moderate, large and subtotal perforations of the tympanic membrane were subjected for tympanoplasty type –I by underlay technique. In 41 patients the temporalis fascia graft was placed with medial (rough) side up (Technique-I) and 39 patients the graft was placed with the lateral (smooth) side up (Technique-II). Results: The graft take up rate was 95.1% in technique-I and 87.2% in technique -II. Failure rate was 4.9% in technique – I and 12.8% in technique – II. Conclusion: Technique – I was judge to be giving better result because: 1.Rough surface of the medial side of the graft after moistening enhances wetting, increases the critical surface tension and broadens the contact surface. 2.The friction due to rough surface resists displacement forces between the graft and remains of the tympanic membrane. 3.Rough surface of the medial side of the temporalis fascia increases the adhesion power and increases the overlap between the two surfaces. To the best of our knowledge this is the only such prospective study for this method.
Keywords: Tympanoplasty; temporalis fascia; underlay grafting